Prediction of quantum spin Hall and Rashba effects in two-dimensional ilmenite oxides - Arokiasamy, Susaiammal (2024)
Using first-principles calculations, we investigate the structural, electronic, and topological properties of two-dimensional (2D) pristine ilmenite oxides ABO3 (A = Au, Ag, or Cu; and B = Bi, Sb, or As) and their corresponding Janus structures. Phonon dispersions reveal the dynamic stability of these compounds. Interestingly, pristine CuBiO3 and AuBiO3, and Janus Cu0.5Ag0.5BiO3, Au0.5Cu0.5BiO3, Au0.5Ag0.5BiO3, and CuBi0.5As0.5O3 are topological insulators, while AuBi0.5As0.5O3, CuBi0.5Sb0.5O3, and AuBi0.5Sb0.5O3 are topological semimetals, as confirmed by their Z2 invariance and conducting edge states under the hybrid functional approach. Moreover, we found van Hove singularities in Au0.5Ag0.5BiO3 and Cu0.5Ag0.5BiO3 near the Fermi level, suggesting the coexistence of superconductivity and nontrivial topology. Finally, isotropic Rashba spin-splitting is studied in detail for Au0.5Ag0.5BiO3. Our findings demonstrate that 2D ilmenite oxides can be a new material playground for potential spintronic applications.